1998
DOI: 10.1021/bi9726234
|View full text |Cite
|
Sign up to set email alerts
|

Groups with Polar Characteristics Can Locate at Both Shallow and Deep Locations in Membranes:  The Behavior of Dansyl and Related Probes

Abstract: To understand the relationship between the chemical structure of polar molecules and their membrane location, the behavior of dansyl (dimethylaminonaphthalenesulfonyl) and related polar fluorescent probes was examined. The depth of these probes in lipid bilayers was determined by parallax analysis of fluorescence quenching [Chattopadhyay and London (1987) Biochemistry 26, 39-45; Abrams & London, Biochemistry (1993) 32, 10826-10831]. Quenching was measured for dansyl groups: (1) attached to the polar headgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…We propose that the tryptophan side chain has a specific affinity for a well defined site near the interface, with the indole imino moiety positioned near the center of the lipid carbonyl region, and the fused aromatic rings in contact with the lipid acyl chains. This location is in good agreement with the membrane depth of NH-containing carbazole indole analogs, as determined by parallax analysis of fluorescence quenching (32,42) but is on average somewhat deeper in the membrane than NMR studies on other small Trp analogs predict (43). In both studies, however, these watersoluble analogs are not part of a transmembraneous peptide.…”
Section: Discussionsupporting
confidence: 80%
“…We propose that the tryptophan side chain has a specific affinity for a well defined site near the interface, with the indole imino moiety positioned near the center of the lipid carbonyl region, and the fused aromatic rings in contact with the lipid acyl chains. This location is in good agreement with the membrane depth of NH-containing carbazole indole analogs, as determined by parallax analysis of fluorescence quenching (32,42) but is on average somewhat deeper in the membrane than NMR studies on other small Trp analogs predict (43). In both studies, however, these watersoluble analogs are not part of a transmembraneous peptide.…”
Section: Discussionsupporting
confidence: 80%
“…The results of the present work are in agreement with studies by fluorescence spectroscopy, which have also shown that several membrane probes may occupy both shallow and deep locations in the bilayer. [3][4][5][6][7] A study with the fluorescent probe 4'-dimethylamino-3-hydroxyflavone in bilayer vesicles of EYPC has shown that the addition of 30 mol % cholesterol induced strong changes in the concentrations of the probe in H-bonded and H-bond free forms, suggesting redistribution of the dye from the membrane surface to the hydrophobic region of the bilayer. 5 Moreover, similar relocations of the probe Prodan caused by cholesterol were also observed in model membranes of phosphatidylcholines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of bilayer systems using fluorescence spectroscopy have also shown that several membrane probes may occupy at least two locations in the bilayer characterized by distinct polarity and hydration. [3][4][5][6][7] The origin of this bimodal distribution has been interpreted based on the ability of these probes to participate in intermolecular hydrogen bonding within the membrane -a polar site at the bilayer interface where the probe is H-bonded to water and an apolar site with no H-bonding to water. 5 Interestingly, hydrostatic pressure applied on multilamellar vesicles of DMPC causes the relocation of the fluorescent probe Prodan towards more hydrophobic environments in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The mean fluorescence lifetime of dansyl-PE was used to evaluate PC head group hydration at the lipid particle surface. Dansyl fluorophores are located at the PC head group region in membranes (36,37), and the lifetime of the excited state reflects their local polarity, to which water is the major contributing factor (38). The mean fluorescence lifetime in TO-PC/Chol emulsions is shorter than that in TO-PC emulsions, indicative of an increase in head group hydration at the TO-PC/Chol emulsion surface.…”
Section: Effects Of Chol On Acyl Chain Order and Head Group Hydrationmentioning
confidence: 99%